HUMAN CELLULAR MODELS FOR RETINAL DISEASE: From Induced Pluripotent Stem Cells to Organoids. Issue 10 (October 2022) - Mustafi, Debarshi; Bharathan, Sumitha P.; Calderon, Rosanna; Nagiel, Aaron
Abstract : The ability to study human retinal disease in vitro has greatly advanced with the advent of stem cell technique and the ability to generate three-dimensional organoids. Generation of stem cells from patients to study them in two and three-dimensional cultures can now allow for a personalized approach to retinal diseases. Abstract : Purpose: To provide a concise review of induced pluripotent stem cells (iPSCs) and retinal organoids as models for human retinal diseases and their role in gene discovery and treatment of inherited retinal diseases (IRDs). Methods: A PubMed literature review was performed for models of human retinal disease, including animal models and human pluripotent stem cell–derived models. Results: There is a growing body of research on retinal disease using human pluripotent stem cells. This is a significant change from just a decade ago when most research was performed on animal models. The advent of induced pluripotent stem cells has permitted not only the generation of two-dimensional human cell cultures such as RPE but also more recently the generation of three-dimensional retinal organoids that better reflect the multicellular laminar architecture of the human retina. Conclusion: Modern stem cell techniques are improving our ability to model human retinal disease in vitro, especially with the use of patient-derived induced pluripotent stem cells. In the future, a personalized approach may be used in which the individual's unique genotype can be modeled in two-dimensional culture or three-dimensional organoids and then rescued with an optimized therapy before treating the patient.